Effectiveness and Advantages of On-Site Pathology Services in the Care of Patients With Nonmelanoma Skin Cancer. Issue 1 (January 2016) - Machan, Mac; Zitelli, John; Brodland, David
Abstract : BACKGROUND: On-site pathology services are an integral part of many dermatology and surgical dermatology practices in the United States. OBJECTIVE: Assess the effectiveness and advantages of on-site pathology services. METHODS: Biopsy data from 7 practices with on-site pathology services were reviewed to determine the diagnostic accuracy of malignancies from all lesional biopsies. Patient preference and convenience were queried and measured with satisfaction surveys. RESULTS: Of note, 1, 052/1, 379 (76.3%) of biopsies demonstrated a malignancy. Most patients underwent treatment of malignant lesions on a different day than the biopsy. Of the patients who scheduled a return visit for surgery on a later date, 42/246 (17.1%) reported incurring additional costs and 44/249 (17.7%) had a relative/friend who was inconvenienced. CONCLUSION: On-site pathology services provide efficient, effective, and convenient care for skin cancer patients. Fellowship-trained dermatologic surgeons use on-site pathology services to diagnose and treat clinically relevant nonmelanoma skin cancer.